Exposure to heavy metals modifies optimal gestational weight gain: A large nationally representative cohort of the Japan Environment and Children's Study. (January 2021) - Jung, Chau-Ren; Nakayama, Shoji F.; Isobe, Tomohiko; Iwai-Shimada, Miyuki; Kobayashi, Yayoi; Nishihama, Yukiko; Michikawa, Takehiro; Sekiyama, Makiko; Taniguchi, Yu; Nitta, Hiroshi; Yamazaki, Shin; ,
Highlights: Concentrations of heavy metals (mercury, lead and cadmium) were measured in 103, 060 pregnant women. Postpartum weight retention and childhood obesity were included in determining optimal GWG. Optimal GWG ranges were altered in women highly exposed to heavy metals. Underweight women with Hg> 5.21 ng/g may not benefit from optimal GWG. Overweight women with Hg of 3.67–5.21 ng/g, Pb > 5.21 ng/g, and Cd > 0.66 ng/g may not benefit from optimal GWG. Abstract: Clinical guidelines including those set by the US Institute of Medicine, have based optimal gestational weight gain (GWG) on maternal pre-pregnancy body mass index (BMI), but have not considered the role of environmental toxicants such as heavy metals that can disrupt these processes. This study designed to determine optimal GWG ranges in women grouped according to BMI, and to assess whether blood concentrations of heavy metals alter the relationships between GWG and outcomes. A total of 103, 060 participants in the Japan Environment and Children's Study recruited between 2011 and 2014 were followed until their children reached 3 years of age. Outcomes included 1 min Apgar score <7, caesarean delivery, childhood obesity, gestational diabetes, pregnancy-induced hypertension, low birth weight, large for gestational age, macrosomia, operative vaginal delivery, postpartum weight retention, preterm birth and small for gestational age. The optimal GWG ranges were determined using multivariate logistic regression models. Stratified analyses were performed to determine optimal GWG ranges according to quartiles of heavy metals. Optimal GWGs for underweight, normal weight and overweight women were found to be 10.0 to <14.0 kg, 6.0 to <12.0 kg and 4.0 to <8.0 kg, respectively. However, the benefits of optimal GWG were attenuated in women exposed to high concentrations of mercury (Hg), lead (Pb) and cadmium (Cd). Despite being within optimal GWG, underweight women with Hg > 5.21 ng/g and overweight women with Hg 3.67–5.21 ng/g, Pb > 7.31 ng/g and Cd > 0.66 ng/g had null effects. Heavy metals can modify the associations between GWG and outcomes, particularly for underweight and overweight women. Because of the complex interactions of environmental toxicants with pre-pregnancy BMI, GWG and adverse outcomes, GWG guidelines should be interpreted cautiously. Environmental toxicants may influence the determination of a clinical guideline.